Left-dislocated free relatives in Old English - Bartnik, Artur (LINGUISTICA SILESIANA, 2023)
This paper investigates left-dislocated free relatives in Old English. On the theoretical level, it contributes to the ongoing discussion on the syntax of free relatives. It confirms a sharp distinction between wh- free relatives and demonstrative free relatives. The former type favours the Comp analysis, whereas the latter class is amenable to both the Comp and Head analyses. On the empirical level, it provides evidence that the Comp analysis with wh- pronouns is selected mainly on the basis of pied piping/stranding facts, while case marking regulates the choice of an appropriate analysis with demonstrative free relatives with þe. This corpus-based study also offers some quantitative information on the frequent patterns and cases commonly found in them.
Keywords: free relative; left-dislocation; case; relative clause; Old English